Analysis of the Agricultural Potential of Papua Province - Sinaga, Irma Lasanova (Journal of International Conference Proceedings, 2023)
Papua is one of the provinces in Indonesia that has enormous agricultural potential because it has very large areas of land. Most of Papua's population works in agriculture. Even though the agricultural sector is still the basis of hope for the majority of the population, its contribution to GRDP is less than 25 percent. For this reason, it is necessary to carry out an analysis to determine the agricultural potential that exists in each regency/city in Papua Province and the basis and non basis agricultural sectors that exist in each regency/city in Papua Province. The analytical methods used in this research are Shift-Share and Location Quotient. The results of the Shift-Share analysis, seen from the total value (Shift Share) of the Agricultural sector in all Regencies/Cities in Papua Province, is positive, which means that the growth of the sector is progressive and has the potential to be developed. Based on the results of the LQ analysis, there are 27 regencies included in the basis sector, which means that these regency have a surplus in their agricultural sector and can meet the needs of their region and other regions. On the other hand, Mimika Regency and Jayapura City are included in the non-base sector.